Thin layer drying of zucchini in solar dryer located in Osmaniye region - Çerçi, Kamil Neyfel (Array, 2018)
In this study, the dehydration behavior of zucchini using solar assisted drying system was examined according to 22 thin layer drying models available in literature. The correlation coefficient (R2), chi-square (χ2) and root mean square error (RMSE) values were calculated to check the suitability of models by non-linear regression analysis. It was found that Cubic and Modified Midilli-1 models were the most suitable equations and their R2 values were calculated as 0.99963. χ2 and RMSE values of related mathematical expressions were 1.89343×10‒5, 1.91692×10‒5 and 0.01685×10‒3, 0.01721×10‒3 respectively. In addition, heat transfer, mass transfer and diffusion coefficients, which were important parameters in design of drying systems were also determined as 5.18124 W/m2°C, 1.57129×10‒7 m/s and 2.335718×10‒9 m2/s respectively.